Hazard Summary Report on the Argonne Low Power Reactor (ALPR) - Argonne National Laboratory. Reactor Engineering Division. (Argonne National Laboratory. Reactor Engineering Division., 1958)
Report regarding a nuclear reactor designed to operate in arctic conditions. This report includes a design of such a reactor and potential hazards.